Concurrent product layout design optimization and dependency management using a modified NSGA-III approach - Law-Kam Cio, Yann-Seing; Beltrame, Giovanni; Vadean, Aurelian; Mohebbi, Abolfazl; Achiche, Sofiane (Frontiers in Mechanical Engineering, 2024)
The complexity of mechatronic systems has increased with the significant advancements of technology in their components which makes their design more challenging. This is due to the need for incorporating expertise from different domains as well as the increased number and complexity of components integrated into the product. To alleviate the burden of designing such products, many industries and researchers are attracted to the concept of modularization which is to identify a subset of system components that can form a module. To achieve this, a novel product-related dependency management approach is proposed in this paper with the support of an augmented design structure matrix. This approach makes it possible to model positive and negative dependencies and to compute the combination potency between components to form modules. This approach is then integrated into a modified non-dominated sorting genetic algorithm III to concurrently optimize the design and identify the modules. The methodology is exemplified through the case study of a layout design of an automatic greenhouse. By applying the proposed methodology to the case study, it was possible to generate concepts that decreased the number of modules from 9 down to 4 while ensuring the optimization of the design performance.